Networking Governance in Handling Stunting in West Java - Fatmawati, Fatmawati; Prila Aulin, Salamandara; Andri, Yayan (Iapa Proceedings Conference, 2024)
Handling stunting in West Java requires cross-sectoral efforts involving all integrated stakeholders through coordination and consolidation of various programs. Mainly in increasing public awareness, health services, and access to clean environment and sanitation. This research analyzes how networking governance in handling stunting in West Java. The research method used is qualitative in the form of data collection techniques, with direct interviews and documentation studies. As well as analyzing data interactively. Meanwhile, for data validity in this study using source triangulation. The results showed that the role of actors in the network for handling stunting in West Java involved multi-stakeholders as a cross-leadership collaboration. In developing the network, it is necessary to involve the role of government, private partners, academics, and the community in managing their resources, implementing plans with a deliberative approach before decision making.